2007
DOI: 10.1021/bm7005517
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Spider Silk Proteins In Situ in the Intact Major Ampullate Gland and in Solution

Abstract: To understand the spinning process of dragline silk by spiders, the protein conformation before spinning has to be determined. Raman confocal spectromicroscopy has been used to study the conformation of the proteins in situ in the intact abdominal major ampullate gland of Nephila clavipes and Araneus diadematus spiders. The spectra obtained are typical of natively unfolded proteins and are very similar to that of a mixture of recombinant silk proteins. Vibrational circular dichroism reveals that the conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 22 publications
8
92
0
2
Order By: Relevance
“…The spidroin remains unassembled and predominantly contains helical shapes (α-helices, turns and 3 10 -helices), as observed in the deconvolution of Raman spectra. 10,56 Our simulations show that helices towards the beginning of the sequence are typically arranged at a ca. 60 degree angle to one another.…”
Section: Size Dependence Of Structural Transition and Shear Stressmentioning
confidence: 80%
See 1 more Smart Citation
“…The spidroin remains unassembled and predominantly contains helical shapes (α-helices, turns and 3 10 -helices), as observed in the deconvolution of Raman spectra. 10,56 Our simulations show that helices towards the beginning of the sequence are typically arranged at a ca. 60 degree angle to one another.…”
Section: Size Dependence Of Structural Transition and Shear Stressmentioning
confidence: 80%
“…[9][10][11] None of the spinning dopes were found to possess silk in β-sheet conformation. The presence of α-helices and left handed 3 10 -helices were identified by Raman microspectrophotmetry, 10 with NMR studies in contrast suggesting the silk is stored in a random coil state. 11 The MaSp sequences were shown to have no natural propensity for aggregation to give β-amyloid structures, a property of importance for silks in biomedical applications.…”
Section: Figure1amentioning
confidence: 99%
“…Taking into consideration that repetitive amino acid sequences are unlikely to adopt an ideal random conformation without any (at least locally) regular structure,45 it would be plausible that PAS polypeptides show a kind of random‐coil structure influenced by the PPII conformation 46. Of note, it has been proposed that the PPII conformation represents the energetically most favored conformation of the peptide bond,47 since solvation of the hydrophilic polypeptide backbone is maximized while putative entropy loss due to formation of secondary structure with more pronounced order (such as α‐helix) is kept minimal.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational circular dichroism and NMR spectroscopy have further shown that the proteins adopt polyproline II (PPII), random coil and a-helix conformations. 72 The Protein Transformation During the Spinning Process in the Ma Gland…”
Section: Structure Of Silk By Raman Spectromicroscopymentioning
confidence: 99%
“…72 The spectrum of FIGURE 8 XX and ZZ polarized spectra of the spinning dope at different locations along the Ma duct's canal of N. clavipes. The probed points are specified with green arrows.…”
mentioning
confidence: 99%